Practical Problems of Giving Opinions by Regional Chambers of Accounting on the Possibility of Repayment of Obligations in Local Government Units - Marcin Tyniewicki (Prawo Budżetowe Państwa i Samorządu)
Opinions of the regional accounting chambers on the possibility of repayment of the credit, loan or redemption of the securities by local government units have some specific features compared with the other opinions concerning the financial management of the local government. Firstly, they are only issued at the request of the unit that they concerned. Secondly, for the reason they relate to public debt issues, to some extent their content may be similar or “partial reproduction” of the standpoint of the regional chamber of accounting within already issued opinions referring to acts on budgetary planning process in local government units. The purpose of this article is to assess the legitimacy of issuing such opinions and to identify the relationship between the ordinances (resolutions) on the possibility of repayment of the credit, loan or redemption of the securities and provisions of local government budget.